Analisis Financial Attitude dan Financial Knowledge Terhadap Financial Management Behavior di Universitas Muhammadiyah Jambi - Mustika Mustika; Mainita Mainita; Aulia Yunita Harly (Universitas Batanghari Jambi, 2023)
The purpose of this study is to investigate and analyze how Muhammadiyah University in Jambi's financial management behavior is impacted by financial knowledge and attitude. According to the results of the descriptive analysis, the participants generally demonstrated a satisfactory degree of financial attitude, financial knowledge, and financial management behavior. Testing specific hypotheses revealed, however, that the financial attitude variable did not significantly and favorably influence university financial management behavior. On the other hand, it has been discovered that financial knowledge has a favorable and considerable impact on financial management behavior. Additionally, it was discovered that financial attitude and financial knowledge strongly influenced financial management behavior at Muhammadiyah University of Jambi when both variables were taken into account combined. Alternatively said, both facets